Energy Consumption of the Russian Road Transportation Sector: Prospects for Inter-Fuel Competition in Terms of Technological Innovation - Dmitriy Grushevenko; Ekaterina Grushevenko; Vyacheslav Kulagin (Foresight and STI Governance)
The development of production and consumption technologies for the road transport has led to large scale introduction of alternative energy in this sector. These alternatives to the conventional petroleum fuels include biofuels, electricity, natural gas and synthetic fuels produced from coal and natural gas. However, it is very important to point out, that inter-fuel competition is determined not only by the development of technologies, but also by such parameters as availability, fuel cost, consumer preferences and government legislations, all of which vary greatly across the globe. In other words, the very same technologies can be capable of radically altering the fuel mix in some countries while having little to none impact in the others. The topic of the inter-fuel competition development in the transportation sector holds much importance for Russia, as the country’s fuels mix is almost totally dominated by the petroleum products. The diversification of energy sources for transport may positively influence energy security and domestic fuels market stability; reduce the strain on ecology, especially in major cities; all the while increasing Russian oil and petroleum products export potential.